Surveying ecolinguistics - Steffensen Sune Vork (Journal of World Languages, 2024)
This article presents a comprehensive and detailed survey of ecolinguistics, defined as an enterprise oriented to how language plays a role in the interactions between human beings, other species, and the natural environment. Since the early 1990s, ecolinguistics has been driven by a concern for life on Earth and as such it comprises the linguistic study of the current ecological crisis. Through a detailed close reading of the literature, in combination with the bibliometric tool of VOSviewer, it surveys eleven subfields of contemporary ecolinguistics. The eleven surveyed subfields of ecolinguistics are: discourse-oriented ecolinguistics, corpus-assisted ecolinguistics, ecostylistics, narratological ecolinguistics, identity-oriented ecolinguistics, ethno-lexical ecolinguistics, ecological discourse analysis, harmonious discourse analysis, cognitive ecolinguistics, educational ecolinguistics, and decolonial/transdisciplinary ecolinguistics. In the conclusion, the article discusses two challenges that face contemporary ecolinguistics: the repetition of certain tropes and narratives about the field, even in the absence of empirical evidence, and the lack of internal debate and critique.